The Influence of Entrepreneurial Behavior and Physical Facilities on Business Success Moderated by Customer Satisfaction at Warung Gak Enak Srengseng, West Jakarta - Diansyah Diansyah; Johanes Hendra Batubara (Budapest International Research and Critics University, 2022)
This research is the effect of entrepreneurial behavior and physical facilities on business success moderated by customer satisfaction at the Warung Gak Enak coffee shop. This research was carried out in several stages, namely the first taken from the bibliography, statistics and collecting the object being researched. Second, to test the feasibility of data and data collection. The third hypothesis testing using SEM PLS. The results of this study are entrepreneurial behavior has a significant effect on business success, physical facilities have a significant effect on business success, customer satisfaction has no significant effect on business success, moderation of customer satisfaction weakens the influence of business behavior on business success and moderation of customer satisfaction can weaken the effect of physical advice on success efforts